Salmonella enterica serovar Virchow bacteremia presenting as typhoid-like illness in an immunocompetent patient - Eckerle, Isabella; Zimmermann, Stefan; Kapaun, Annette; Junghanss, Thomas (Journal of clinical microbiology, 2010)
We report a typhoid-like illness with fever and altered consciousness in a 22-year-old man with growth of Salmonella enterica serovar Virchow in blood and stool culture. Bacteremia and invasive disease due to non-typhoid salmonellae (NTS) are known in severely immunocompromised patients, but so far have not been described in immunocompetent adults.
Gesehen am 28.02.2023